Исследование процесса истечения струи жидкости из отверстия перфорированной оболочки приллера - Скиданенко, М. С.; Склабинский, В. И.; Кононенко, Н. П. (НТУ "ХПИ", 2014)
В статье рассмотрены результаты теоретических и экспериментальных исследований процесса нестационарного истечения струи жидкости из отверстия, что является базовым для расчета виброгранулятора. Определена закономерность регулируемого распада струй жидкости на капли и проведенны исследования, которые подтверждают возможность создания грануляторов розплава, для получения продукта в узком фракционном диапазоне

Stream jet breakup on drops regularity and the performed research prove that it is possible to design such granulator for fusion of nitrogen fertilizers which enables to get granules in a narrow fraction range, with the maximum number of particles which can be cooled off in the tower. One can control size of the drops depending on the temperature of cooling agent supplying into the tower. As a result, the heat load on the tower will be close to the optimal one, thus adhesion of the particles on the working surfaces of the tower is reduced, and as a result, it helps to reduce the cost of energy for processing substandard product and to reduce nitrogen fertilizers dust emissions into the atmosphere, so it will improve the environmental situation in the production area
Analysis of the liquid stream efflux out of the priller perforated case
Keywords: вынужденные возмущения; виброгранулятор; распад струи; экспериментальные исследования; грануляционная башня; forced agitations; vibro-granulator; jet disintegration; experimental research; prilling tower